2012
DOI: 10.2310/jim.0b013e31824e9900
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Angiopoietin-Related Growth Factor (AGF) are Increased in Polycystic Ovary Syndrome

Abstract: Serum AGF levels were paradoxically increased in patients with PCOS in comparison with data of animal experiments. Further studies are needed to better elucidate the physiologic significance of circulating AGF in human disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Recently, the serum ANGPTL6 levels of healthy individuals and patients with different metabolic diseases were assessed. Intriguingly, the serum ANGPTL6 levels were high in individuals who diagnosed with preeclampsia [15], polycystic ovary syndrome [16], and type 2 diabetes mellitus [1718]. Moreover, the serum ANGPTL6 levels of patients with metabolic syndrome was high [19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the serum ANGPTL6 levels of healthy individuals and patients with different metabolic diseases were assessed. Intriguingly, the serum ANGPTL6 levels were high in individuals who diagnosed with preeclampsia [15], polycystic ovary syndrome [16], and type 2 diabetes mellitus [1718]. Moreover, the serum ANGPTL6 levels of patients with metabolic syndrome was high [19].…”
Section: Introductionmentioning
confidence: 99%
“…Kadomatsu et al suggested that ANGPTL6 resistance is likely to occur in obesity or diabetes 9 . ANGPTL6 levels were high in individuals who diagnosed with preeclampsia 10 , polycystic ovary syndrome 11 , and diabetes mellitus 6,8,13 .…”
Section: Discussionmentioning
confidence: 99%
“…132 In addition, exogenous AGF protein inhibits hepatic glucose production and decreased body weight. 133 Despite its beneficial effects on metabolism, serum levels of AGF were elevated in polycystic ovarian syndrome, 134 diabetes, 135 and metabolic syndrome, 136 similar to FGF21 or GDF15. Kim et al 137 observed that high fat diet increased hepatic AGF expression, that was reduced by exercise training.…”
Section: Agf (Angptl6)mentioning
confidence: 99%